2018
DOI: 10.7181/acfs.2017.01396
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of post-traumatic hematoma and fibrosis using hyaluronidase injection

Abstract: Patients complaining of swelling and hematoma caused by contusion of the face can be easily seen in the emergency room. Most of the treatments were conservative treatments such as ice bag application, mild compression dressing, and massage. During the follow-up, fibrosis progression due to hematoma was frequently observed in the contusion site. When hematoma or fibrosis is confirmed, hyaluronidase (H-lase) 1,500 IU and 2 mL of normal saline were mixed and subcutaneously injected in crisscross manner. To evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…For several years, hyaluronidase has been used in various fields of medicine to minimize postoperative edema. Han et al 17 reported injecting hyaluronidase after hematoma and fibrosis due to facial trauma, which resulted in complete resolution of the hematoma, reduced fibrosis, and alleviation of pain. Because nasal bone fractures require surgery after edema is reduced, a considerable amount of time is required between the accident and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For several years, hyaluronidase has been used in various fields of medicine to minimize postoperative edema. Han et al 17 reported injecting hyaluronidase after hematoma and fibrosis due to facial trauma, which resulted in complete resolution of the hematoma, reduced fibrosis, and alleviation of pain. Because nasal bone fractures require surgery after edema is reduced, a considerable amount of time is required between the accident and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and clinical studies have documented the consequent anti-edema effect of HUD 12 , 26 , 27 . By resolving ground substance of the connective tissue, HUD was shown to be effective in early treatment of hematoma and fibrosis 28 , 29 . Furthermore, HUD regulates inflammatory response by decreasing the infiltration of inflammatory mediators such as neutrophils to the inflammatory site 8 or increasing anti-inflammatory cytokines including TNFα (tumor necrosis factor alpha), interleukin (IL)-1α, IL-4, and IL-10, thus promoting wound healing 10 .…”
Section: Discussionmentioning
confidence: 99%
“…9 Isso acontece devido a uma resposta exagerada à cicatrização de feridas ou a um hematoma não reconhecido e não tratado? 3 Alguns autores defendem que os pacientes não se incomodam com os nódulos. 11 Essa não é nossa experiência.…”
Section: Discussionunclassified
“…Os pequenos são geralmente reabsorvidos espontaneamente 2 , mas, em alguns casos, podem induzir complicações. 2,3 A evolução do hematoma compreende três etapas: Estágio I (formação inicial): ferida inchada, quente e flutuante. Requer intervenção imediata.…”
Section: Introductionunclassified